Design Robot Hand Pneumatic System Simulation Using PLC Control for Mechatronics Learning Applications - Rusadi Rusadi; Hadimi Hadimi; Edi Karyadi (Politeknik Negeri Pontianak, 2022)
The Pneumatic System is a power transfer system utilizing compressed air as an intermediate medium. In conventional operation it is operated fully pneumatically or in combination with electricity (electropneumatic). In recent years it can be combined and controlled with a programmable logic controller (PLC). The operation of the pneumatic system with the PLC control system is carried out by desaign a program with a program language, one of which is the Ladder Diagram accompanied by I/O addressing, then the result design program must be transferred to the PLC as the controller of the pneumatic system in this case the controller. robot hand. This study aims to obtain a pneumatic robot hand circuit and a series of ladder diagram programs to control the PLC system in the robot's hand. The results of this research can be used as a reference in designing a pneumatic system with PLC control in the future.